2015
DOI: 10.1089/end.2014.0858
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Operating Room Costs Through Real-Time Cost Information Feedback: A Pilot Study

Abstract: Objective: To create a protocol for providing real time operating room cost feedback to surgeons.We hypothesize that this protocol will reduce costs in a responsible way without sacrificing quality of care.Methods: All operating room costs were obtained and recorded for robotic partial nephrectomy and laparoscopic donor nephrectomy. Prior to the beginning of this project, costs pertaining to the 20 most recent cases were analyzed. Items were identified from previous cases as modifiable for replacement or omiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 3 publications
(2 reference statements)
0
20
0
1
Order By: Relevance
“…Banka et al found that HCAHPS scores improved as a result of real‐time feedback given to residents, but the study was not randomized, utilized a pre‐post design that resulted in there being differences between the patients studied before and after the intervention, and did not provide patient‐specific data to the residents. Tabib et al found that operating costs decreased 17% after instituting real‐time feedback to providers about these costs. Reeves et al conducted a cluster randomized trial of a patient feedback survey that was designed to improve nursing care, but the results were reviewed by the nurses several months after patients had been discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Banka et al found that HCAHPS scores improved as a result of real‐time feedback given to residents, but the study was not randomized, utilized a pre‐post design that resulted in there being differences between the patients studied before and after the intervention, and did not provide patient‐specific data to the residents. Tabib et al found that operating costs decreased 17% after instituting real‐time feedback to providers about these costs. Reeves et al conducted a cluster randomized trial of a patient feedback survey that was designed to improve nursing care, but the results were reviewed by the nurses several months after patients had been discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Operating time is a valuable factor in health care economics, ranges approximately from 750 to 2200 dollars per hour operating time in USA & Europe [ 19 23 ]. In addition, less operating time may accomplish increased surgical efficiency, volume of performed cases, and reduction of patient’s waiting list, especially in high volume setting centres [ 19 22 ]. Our results showed that there is a statistically significant difference between operating time for endoscopic DCR using the drill compared with kerrison punch.…”
Section: Discussionmentioning
confidence: 99%
“…Dashboards also serve to increase surgeon awareness of their costs and have demonstrated cost improvements since rollout. For example, Tabib et al also looked to improve efficacy of healthcare spending by reducing operating room costs with real-time, surgeon-specific feedback on procedure expenses [ 43 ]. In this study, urologists successfully reduced operating room cost using immediate feedback and cost comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals' performances were identifiable amongst colleagues, and this transparency enabled collaboration in identifying areas for cost reduction and implementing appropriate changes. Tabib concluded that the transparency in their methods successfully altered surgeon behavior but noted that further studies are necessary to show equivalence in patient outcomes [ 43 ].…”
Section: Resultsmentioning
confidence: 99%